CDBA Based Universal Inverse Filter. (17th March 2013) - Pandey, Rajeshwari; Pandey, Neeta; Negi, Tushar; Garg, Vivek
Abstract : Current difference buffered amplifier (CDBA) based universal inverse filter configuration is proposed. The topology can be used to synthesize inverse low-pass (ILP), inverse high-pass (IHP), inverse band-pass (IBP), inverse band-reject (IBR), and inverse all-pass filter functions with appropriate admittance choices. Workability of the proposed universal inverse filter configuration is demonstrated through PSPICE simulations for which CDBA is realized using current feedback operational amplifier (CFOA). The simulation results are found in close agreement with the theoretical results.